2017
DOI: 10.1371/journal.pone.0186404
|View full text |Cite
|
Sign up to set email alerts
|

Slower is not always better: Response-time evidence clarifies the limited role of miserly information processing in the Cognitive Reflection Test

Abstract: We report a study examining the role of ‘cognitive miserliness’ as a determinant of poor performance on the standard three-item Cognitive Reflection Test (CRT). The cognitive miserliness hypothesis proposes that people often respond incorrectly on CRT items because of an unwillingness to go beyond default, heuristic processing and invest time and effort in analytic, reflective processing. Our analysis (N = 391) focused on people’s response times to CRT items to determine whether predicted associations are evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 66 publications
(90 reference statements)
6
53
1
Order By: Relevance
“…Other potential support comes from latency studies. A number of studies reported that correct "5 cents" responses take considerably longer than incorrect "10 cents" responses (e.g., Alós-Ferrer, Garagnani, & Hügelschäfer, 2016;Johnson, Tubau, & De Neys, 2016;Stupple, Pitchford, Ball, Hunt, & Steel, 2017;Travers, Rolison, & Feeney, 2016). For example, in one of our own studies we observed that correct responders needed on average about a minute and a half to enter their response whereas incorrect responders only took about 30 seconds (Johnson et al, 2016).…”
Section: Introductionmentioning
confidence: 44%
See 1 more Smart Citation
“…Other potential support comes from latency studies. A number of studies reported that correct "5 cents" responses take considerably longer than incorrect "10 cents" responses (e.g., Alós-Ferrer, Garagnani, & Hügelschäfer, 2016;Johnson, Tubau, & De Neys, 2016;Stupple, Pitchford, Ball, Hunt, & Steel, 2017;Travers, Rolison, & Feeney, 2016). For example, in one of our own studies we observed that correct responders needed on average about a minute and a half to enter their response whereas incorrect responders only took about 30 seconds (Johnson et al, 2016).…”
Section: Introductionmentioning
confidence: 44%
“…The problem background turned yellow 2 seconds before the deadline. Note that previous studies that adopted a free response format without time-restrictions reported average response latencies for correct answers of over 30 s (Stupple et al, 2017;Johnson et al, 2016). Hence, by all means the 10 s deadline remains challenging.…”
Section: Materials and Proceduresmentioning
confidence: 95%
“…However, armed with PD's greater clarity, we expected arithmetic 7 Baron and colleagues also measured dilemma judgment response-times. Given that research shows only a weak correlation between response-times and other measures of reflection (Stupple, Pitchford, Ball, Hunt, & Steel, 2017) and no significant difference in response-times between CRT takers whose first response is correct and CRT takers whose first response is incorrect (Szaszi, Szollosi, Palfi, & Aczel 2017), we did not assess reaction times in the current work.…”
Section: The Current Researchmentioning
confidence: 99%
“…Other studies contradict these findings. Stupple et al () found that quicker response times were not related to intuitive responses on the CRT. Baron et al () said they “failed to find any evidence that the overriding of intuitive responses is relevant to the CRT's predictive power” (p. 279).…”
Section: Introductionmentioning
confidence: 99%